Efeitos da senescência no núcleo supraquiasmático do sagui (Callithrix Jacchus): plasticidade morfológica e neuroquímica - Engelberth, Rovena Clara Galvão Januário (2013)
The circadian timing system (CTS) is responsible for the generation and synchronization and the suprachiasmatic nucleus (SCN) of the hypothalamus has been described as the major circadian pacemaker in many mammalian species. The internal temporal organization managed by SCN is disturbed with aging bringing many pathological disorders that range from loss of complex cognitive performance to simple physiological functions. Therefore, our aim was perform a comparative study of the morphological aspects and neurochemical composition in the SCN of marmosets (Callithrix jacchus) adults and older using immunohistochemical techniques. We found morphometric and neurochemical changes in th SCN o folder animals in comparison to adults, among these a possible decreased in retinal projection to the SCN of older animals, found through a decline in CTB immunostaining, which can occur due atrophy and/or decreasing of fibers from the retinohypothalamic tract (RHT). The Klüver-Barrera histological technique strongly suggests a decrease in those fibers from RHT. Also, by means of a morphometric study, it is found a atrophy and numerical decline of neurons in SCN of aged animals, investigated by Nissl technique, and immunostaining with NeuN and calbindin. Relative optical density (ROD) analysis were used to evaluate the expression of some neurochemical components in SCN, such as GFAP expression, which was increased in older, result that indirectly reinforces that morphological changes occurs due the aging; the vasoactive intestinal polipeptide (VIP) showed no expression alteration in SCN of older animals; the serotonin (5-HT) was descreased in the dorsomedial portion of the SCN, and neurpeptide Y (NPY) apparently also decrease due to the increase of age. Many of these modifications were seen in other animals, such as rodents, human primates and non-human primates. These data about marmoset comes to add new information of the effect of aging on structures responsibles for the circadian rhytmicity, and that some behavioral changes controlled by th SCN, and founded in aged animals, may be caused by these morphological and neurochemical changes. Although some results have been quantitatively negative, qualitatively all analysis show significant change comparing adult and older animals, perhaps due to a low sampling number. In conclusion, the marmoset presents several morphological and neurochemical changes in the SCN of aged animals compared to adults, which may result in behavioral changes that favor pathology aging related